Perceptual Learning and Feature-Based Approaches to Concepts – A Critical Discussion - Stöckle-Schobel, Richard (Frontiers in Psychology, 2012)
A central challenge for any theory of concept learning comes from Fodor’s argument against the learning of concepts, which lies at the basis of contemporary computationalist accounts of the mind. Robert Goldstone and his colleagues propose a theory of perceptual learning that attempts to overcome Fodor’s challenge. Its main component is the addition of a cognitive device at the interface of perception and conception, which slowly builds ‘cognitive symbols’ out of perceptual stimuli. The main mechanisms of concept creation are unitisation and differentiation. In this paper, I will present and examine their theory, and will show that two problems hinder this reply to Fodor’s challenge from being a successful answer to the challenge. To amend the theory, I will argue that one would need to say more about the input systems to unitisation and differentiation, and be clearer on the representational format that they are able to operate upon. Until these issues have been addressed, the proposal doesn’t deploy its full potential to threaten a Fodorian position.